Carisoprodol Abuse in Adolescence - Gupta, Mayank (Cureus, 2020)
Carisoprodol (i.e. Soma, Soprodol, Vanadom) is a muscle relaxant prescribed to relieve symptoms of muscle pain. Carisoprodol's addiction potential in adults has been well-established through case reports in the past. Carisoprodol abuse in adolescents has been reported in the ‘Monitoring the Future’ study since 2007, but no case studies or research has been published to date. Due to its relatively short half-life, tolerance and dependence develop quite quickly, leading to negative mental health outcomes. Awareness and education among health care providers remain critical to screen and treat this condition.